Teknologi Sebagai Media Pembelajaran - Rusna Gani (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2022)
The existence of this media innovation, is expected to improve the teaching and learning process for teachers and students, can be more effective and encourage student creativity. Another advantage is the savings in operational costs of learning and simplifying the preparation of teachers in teaching. In addition, it will facilitate assessment, overcome the limitations of learning media that are not available, and hopefully increase student knowledge. While IT-based learning media is a tool used in the learning process by utilizing information technology. In this system the interaction between teachers (teachers) and participants (students) does not have to meet each other physically as in the conventional education system, they meet in the information technology room (internet) by utilizing a media called a computer. Some media that can be used in IT-based learning, for example; TV, computers.